Differential Evolution of α-Glucan Water Dikinase (GWD) in Plants - Adegbaju, Muyiwa S. (Plants (Basel), 2020)
The alpha-glucan water dikinase (GWD) enzyme catalyzes starch phosphorylation, an integral step in transitory starch degradation. The high phosphate content in stored starch has great industrial value, due to its physio–chemical properties making it more versatile, although the phosphate content of stored starch varies depending on the botanical source. In this study, we used various computational approaches to gain insights into the evolution of the GWD protein in 48 plant species with possible roles in enzyme function and alteration of phosphate content in their stored starch. Our analyses identified deleterious mutations, particularly in the highly conserved 5 aromatic amino acid residues in the dual tandem carbohydrate binding modules (CBM-45) of GWD protein in C. zofingiensis, G. hirsutum, A. protothecoides, P. miliaceum, and C. reinhardtii. These findings will inform experimental designs for simultaneous repression of genes coding for GWD and the predicted interacting proteins to elucidate the role this enzyme plays in starch degradation. Our results reveal significant diversity in the evolution of GWD enzyme across plant species, which may be evolutionarily advantageous according to the varying needs for phosphorylated stored starch between plants and environments.